Resonance of Islamic Economics on the Stage of Globalization - Imama Zuchroh (PT. Hafasy Dwi Nawasena, 2023)
This research aims to investigate and describe the global influence of Islamic economics in the context of the growing phenomenon of globalization. Using a descriptive qualitative approach, data was collected through literature study, document analysis, as well as interviews with economic experts and Islamic economic practitioners. Data analysis was conducted by considering key concepts in Islamic economics and how they interact with the current globalization process. The research findings show that Islamic economics has significant resonance on the globalization stage, influencing economic policies, business practices, and economic thinking at large. The contribution of Islamic economics to sustainable development, economic inclusiveness, and social justice is increasingly recognized and applied in various global contexts. However, challenges and constraints in the implementation of Islamic economic concepts are also found, including the gap between theory and practice, as well as the integration of Islamic economics with the dominant conventional economic system. The implications of this study highlight the importance of understanding and applying Islamic economic principles effectively in facing complex global challenges, by strengthening the role of Islamic economics in creating a sustainable positive impact amidst globalization.